Self-adjuvanting C18 lipid vinil sulfone-PP2A vaccine: study of the induced immunomodulation against Trichuris muris infection. Issue 4 (12th April 2017) - Gomez-Samblas, M.; García-Rodríguez, J. J.; Trelis, M.; Bernal, D.; Lopez-Jaramillo, F. J.; Santoyo-Gonzalez, F.; Vilchez, S.; Espino, A. M.; Bolás-Fernández, F.; Osuna, A.
Abstract : Abstract : Despite the importance of the adjuvant in the immunization process, very few adjuvants merge with the antigens in vaccines. A synthetic self-adjuvant oleic-vinyl sulfone (OVS) linked to the catalytic region of recombinant serine/threonine phosphatase 2A from the nematode Angiostrongylus costaricensis (rPP2A) was used for intranasal immunization in mice previously infected with Trichuris muris . The animal intranasal immunization with rPP2A-OVS showed a reduction of 99.01% in the number of the nematode eggs and 97.90% in adult. The immunohistochemical analysis of the intestinal sections showed that in immunized animals with lipopeptide the mucus was significantly higher than in the other experimental groups. Also, these animals presented significantly different chemokine, CCL20 and CCL11, levels. However, although the number and size of Tuft cells did not vary between groups, the intensity of fluorescence per cell was significant in the group immunized with the rPP2A-OVS. The results of the present study suggest that mice immunized with the lipopeptide are capable of activating a combined Th17/Th9 response. This strategy of immunization may be of great applicability not only in immunotherapy and immunoprophylaxis to control diseases caused by nematodes but also in pathologies necessitating action at the level of the Th9 response in the intestinal mucosa.